The Relation of Androgenetic Alopecia Severity with Epicardial Fat Thickness - Colgecen, Emine (Ann Dermatol, 2016)
BACKGROUND: Androgenetic alopecia (AGA) is the most commonly encountered baldness pattern in men. Epicardial fat tissue is found on the cardiac surface between the myocardium and visceral pericardium. Both AGA and epicardial fat thickness (EFT) are related to coronary artery disease, which is also reflected by an increase in carotid intima media thickness (CIMT). OBJECTIVE: The purpose of this study was to investigate the relation of AGA severity with EFT. METHODS: One hundred twenty-six male patients with AGA aged 18 to 55 years without histories of chronic disease were enrolled. Subjects were divided into three groups (mild, moderate, and severe) on the basis of the Hamilton baldness scale as modified by Norwood. Maximum EFT was measured at end-systole on the midventricular free wall of the right ventricle. CIMT was also recorded for all patients. RESULTS: The groups did not have statistically significant differences with respect to age, height, weight, body mass index, left ventricular ejection fraction, or left atrial diameter (p>0.05 for all comparisons), but the severe group had a higher EFT compared with the moderate (p<0.001; z score, -7.040) and mild groups (p<0.001; z score, -6.667). The moderate group also had higher EFT than the mild group (p<0.001; z score, -5.931). Mean CIMT value in the severe group was significantly higher compared with the value in the other groups. CONCLUSION: The study showed that subjects in advanced stages of AGA had increased EFT, which was measured via echocardiography.